An Analysis of Figurative Language in The Song Lyrics By Saif Adam - Hayati Milana; Havid Ardi (English Language and Literature, 2020)
AbstractThe aim of this study was to identify the types of figurative language used in the lyric of Saif Adam songs and the dominant types of figurative language found in the lyric of Saif Adam songs. The method used in this study is a descrptive qualitative method. This research used the theory of Perrine. The researcher found 8 types of figurative language used in Saif Adam’s song lyrics such as hyperbole, irony, metaphor, personification, simile, litotes, metonymy, and paradox. The data were collected by reading the lyrics of Saif Adam’s song. There were 14 of hyperbole, 3 of Irony, 20 of metaphor, 11 of personification, 10 of simile, 5 of litotes, 10 of metonymy, and 7 of paradox. This study found that the most dominant type of figurative language was metaphor with the percentage of 25%. It was followed by hyperbole with the percentage of 17.5%. Then, it was followed by personification with percentage 13.75%,. simile and metonymy with the percentage of 11.3%. And also it was followed by paradox and litotes with the proportion of 7.9% and 5.6%. Irony was the least dominant one with the percentage of only 3.4%.Key words :  Semantics, Figurative language, Song, Religious Song, Lyric.